2023
DOI: 10.1038/s41598-023-30576-1
|View full text |Cite
|
Sign up to set email alerts
|

Virus-free transfection, transient expression, and purification of human cardiac myosin in mammalian muscle cells for biochemical and biophysical assays

Abstract: Myosin expression and purification is important for mechanistic insights into normal function and mutation induced changes. The latter is particularly important for striated muscle myosin II where mutations cause several debilitating diseases. However, the heavy chain of this myosin is challenging to express and the standard protocol, using C2C12 cells, relies on viral infection. This is time and work intensive and associated with infrastructural demands and biological hazards, limiting widespread use and hamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…We specifically proposed that the double mutation R243E/E466R in cardiac myosin II could be useful [89] and preferred over the single R243E mutation (disrupting the secondary Pi-site) because the double mutation is expected to preserve other aspects of actomyosin function. [89] We have found that both the R243E and R243E/E466R mutations are properly transfected into C2C12 cells by a new virus free method [90] that would allow convenient screening of a wide range of mutants. Both mutants also express well (Figure S2).…”
Section: Multistep Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We specifically proposed that the double mutation R243E/E466R in cardiac myosin II could be useful [89] and preferred over the single R243E mutation (disrupting the secondary Pi-site) because the double mutation is expected to preserve other aspects of actomyosin function. [89] We have found that both the R243E and R243E/E466R mutations are properly transfected into C2C12 cells by a new virus free method [90] that would allow convenient screening of a wide range of mutants. Both mutants also express well (Figure S2).…”
Section: Multistep Modelmentioning
confidence: 99%
“…We have found that both the R243E and R243E/E466R mutations are properly transfected into C2C12 cells by a new virus free method [ 90 ] that would allow convenient screening of a wide range of mutants. Both mutants also express well (Figure S2).…”
Section: Testing the Alternative Models For Pi‐releasementioning
confidence: 99%
“…Dim fluorescence of GFP in GFP hybrids is most likely the consequence of large cytoplasmic volume and high number of nuclei in a single cytoplasm which are interrupting normal cell function required for proper expression of GFP. The situation might be specific for artificialy obtained polynucleated cells as such situation was not observed in naturally polynucleated muscle cells (Velayuthan et al, 2023).…”
Section: Resultsmentioning
confidence: 97%
“…We have found that both the R243E and R243E/E466R mutations are properly transfected into C2C12 cells by a new virus free method [76] that would allow convenient screening of a range of mutants. Both mutants also express well in these cells (Fig.…”
Section: Testing the Alternative Models For Pi-releasementioning
confidence: 99%